Kesesuaian Pencatatan Aset Biologis pada Peternakan Rakyat dengan SAK EMKM: Studi Kasus Peternakan Multi-Spesies di Cileunyi, Kabupaten Bandung - Ihsan Ihsan; Risma Nur Arifah; Shaumy Adellya Novianti; Yati Nurhajati (INDO PUBLISHING, 2026)
This study aims to analyze the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the recording and reporting of biological assets at Pak Ahnu's Livestock Farm, an MSME entity with annual turnover below IDR 4,800,000,000. SAK EMKM is the appropriate accounting standard for small and medium-scale enterprises as it employs a historical cost approach that is simpler, practically applicable, and does not require the use of fair value measurement as mandated by PSAK 241 which is intended for large-scale entities. A mixed-method qualitative-quantitative case study design with a descriptive analytical approach was adopted. Data were collected through field observation, in-depth interviews with the farm owner, and analysis of internal financial documents. The results reveal that Pak Ahnu's Livestock manages total biological assets valued at IDR 134,000,000 comprising horses (IDR 40,000,000), sheep (IDR 42,000,000), goats (IDR 46,000,000), and immature livestock (IDR 6,000,000). Monthly revenue reaches IDR 10,800,000, with net profit per head of IDR 1,925,926 for male sheep and IDR 925,926 for female sheep. Findings indicate that the farm's current bookkeeping practices are not fully aligned with SAK EMKM, particularly in the absence of separate accounts for productive and consumable biological assets, lack of depreciation calculation for long-term productive animals, and the absence of complete financial statements comprising the Statement of Financial Position and Statement of Profit or Loss in the SAK EMKM format. Key recommendations include disciplined historical cost-based recording, preparation of two-component financial statements per SAK EMKM, and basic bookkeeping training for the owner.